Pride [videorecording (DVD)] - Gonera, Sunu; Howard, Terrence; Mac, Bernie; Elise, Kimberly, 1971- (Lionsgate, 2007)
Based on the true story of inner city Philadelphia swim coach Jim Ellis. The story revolves around Ellis' fight to build a swim team in one of Philly's toughest neighborhoods in the 1970s. Ultimately, Ellis leads the swimmers to the state championships.